Accuracy of different oxygenation indices in estimating intrapulmonary shunting at increasing infusion rates of dobutamine in horses under general anaesthesia. Issue 3 (June 2015) - Briganti, A.; Portela, D.A.; Grasso, S.; Sgorbini, M.; Tayari, H.; Bassini, J.R. Fusar; Vitale, V.; Romano, M.S.; Crovace, A.; Breghi, G.; Staffieri, F.
Highlights Dobutamine infusion profoundly affects oxygen extraction in horses anaesthetised with isoflurane. All the OTIs tested in this study demonstrated a poor correlation with the Qs/Qt. F-shunt is the most reliable OI for the estimation of Qs/Qt independent of the haemodynamic conditions of the patient. OTIs should be used cautiously in horses under isoflurane anaesthesia.